A Review on Polymer/Cement Composite with Carbon Nanofiller and Inorganic Filler. (12th August 2016) - Afzal, Anam; Kausar, Ayesha; Siddiq, Muhammad
ABSTRACT: Owing to non-toxicity and biocompatibility, water-soluble polymers (polyethylene glycol, polyvinyl alcohol, poly( N -isopropylacryl-amide), and polyvinylpyrrolidone) have different applications in civil engineering, paint industry, and environmental industries. Portland cement is made up of various kinds of components such as concrete, mortar, and stucco. The quality of cement can be enhanced by adding different fillers such as slag, silica fume, fly ash, and natural pozzolan. Carbon nanofillers (carbon nanotube and graphite) and inorganic fillers such as CaCO3, Mg(OH)2, talc, and mica are used in polymer/cement composites to enhance their properties. Polymer/cement composite with lightweight aggregates are best for several future composite applications. GRAPHICAL ABSTRACT: